2011
DOI: 10.1038/onc.2011.71
|View full text |Cite
|
Sign up to set email alerts
|

Camptothecin-induced downregulation of MLL5 contributes to the activation of tumor suppressor p53

Abstract: Mixed lineage leukemia 5 (MLL5) has been implicated in multiple aspects of cell physiology, such as hematopoiesis, cell cycle control and chromatin regulatory network. In this study, we present evidence that MLL5 is involved in the camptothecin (CPT)-induced p53 activation. CPT promoted the degradation of MLL5 protein in a time-and dose-dependent manner in actively replicating cells. The downregulation of MLL5 led to phosphorylation of p53 at Ser392, which was abrogated by exogenous overexpression of MLL5. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 54 publications
(75 reference statements)
1
10
0
2
Order By: Relevance
“…Two genes including Zbtb20 34,35 and Ankrd17 36,37 are involved in hepatocyte differentiation and maturation, while Zbtb20 is a transcription factor that represses the expression of α-fetoprotein, a widely used biomarker used for HCC surveillance. The Setd2 TS gene 38 and the putative TS genes Adk 39 , Dpyd 40,41 , Mll5 42 and Nfia 43,44 were also identified as potential driver genes for HCC, although there is no published evidence they are involved in HCC. Six driver genes also regulate hepatic metabolism with Pten 45 , Gsk3b 46 , Adk 47,48 , Zbtb20 49 and Ghr 50,51 regulating lipid and glucose metabolism, and Dpyd controling pyrimidine catabolism in hepatocytes.…”
Section: Resultsmentioning
confidence: 99%
“…Two genes including Zbtb20 34,35 and Ankrd17 36,37 are involved in hepatocyte differentiation and maturation, while Zbtb20 is a transcription factor that represses the expression of α-fetoprotein, a widely used biomarker used for HCC surveillance. The Setd2 TS gene 38 and the putative TS genes Adk 39 , Dpyd 40,41 , Mll5 42 and Nfia 43,44 were also identified as potential driver genes for HCC, although there is no published evidence they are involved in HCC. Six driver genes also regulate hepatic metabolism with Pten 45 , Gsk3b 46 , Adk 47,48 , Zbtb20 49 and Ghr 50,51 regulating lipid and glucose metabolism, and Dpyd controling pyrimidine catabolism in hepatocytes.…”
Section: Resultsmentioning
confidence: 99%
“…Immunoprecipitation and in-vitro pull down experiments showed that MLL5 interacts with borealin, a subunit of the chromosome passenger complex, stabilizing the complex [18]. MLL5 is also reported to bind with tetrameric p53 via p53's DNA binding domain [19]. MLL5 is a component of a complex associated with retinoic acid receptor that requires GlcNAcylation of its SET domain in order to activate its histone lysine methyltransferase activity [20].…”
Section: Introductionmentioning
confidence: 99%
“…18, 31 We performed cell cycle analyses following treatment with PBS, free CPT, CPT-G4.5-PEG or dendrimer carrier. As shown in Figure 6, cells treated with free CPT or CPT-G4.5-PEG conjugate exhibited a remarkable decrease in the G 0 /G 1 cell population and an increase in G 2 /M going from a little more than 20% to more than 40% over a period of 24 h. Untreated cells (PBS group) showed a normal cell cycle distribution with a larger fraction in the G 0 /G 1 phase.…”
Section: Resultsmentioning
confidence: 99%
“…1-3 Thus, various dendrimer-based drug delivery platforms have been developed 4-7 , and their utility for delivering anticancer drugs _ENREF_18 _ENREF_19 has been actively explored and yielded promising results. 8-14 _ENREF_20 _ENREF_18 Regardless, a commonly encountered problem is the heterogeneity of ligand and drug on the dendrimer surface during chemical synthesis. 15 It is essential to obtain a uniform distribution of ligand and drug for standardizing therapeutic effects and for the successful translation of dendrimer-based nanomedicines to clinical application.…”
Section: Introductionmentioning
confidence: 99%